FEBRIANTI YULI SATRIYANI - admin, Keguru (KEGURU "Jurnal Ilmu Pendidikan Dasar", 2019)
AbstractLearning motivation plays an important role in learning activities, which makes students feelexcited in learning activities so they can produce good learning outcomes. During this time the learningactivities in PGSD Study Program are still dominantly done conventionally with lecturers as the main actorsin lecture activities. From the results of observations and interviews, data were obtained that studentspreferred student centered based learning and they were actively involved in learning activities. This studyaims to describe, (1) the implementation of learning by using flash cards and asking and giving questionmethods in learning and learning courses in first semester students of the Primary teacher education studyprogram University Trilogy Study Program, and (2) the effect of implementing learning using flash cardmedia and asking and giving question method on learning and learning courses in first semester students ofPGSD University Study Program Trilogy towards increasing student learning motivation.The approach used in this study is qualitative research with a type of classroom action research.Data collection techniques are carried out by observation, interviews, and documentation. The data analysistechnique used is descriptive qualitative using the Kemmis and Taggart models which include: (1) planning,(2) implementation of actions, (3) observation (observation), and (4) reflection.The results of the study show that the application of Flash Card Media and Asking and GivingQuestion Methods in Learning and Learning Courses can increase students' learning motivation. They allseemed to actively construct their own knowledge, through meaningful learning activities by contributingstudents in making questions and answers to the flash card and then randomly making a asking and givingquestion to their classmates. The learning atmosphere looks active, students look enthusiastic in learningactivities. Suggestions based on this research are to disseminate ways to make flash card media and improvethe assessment method in applying asking and giving question activities.